Contrast-enhanced ultrasound reveals perfusion differences between benign lipoma and semi-malignant atypical lipomatous tumors: a prospective clinical study = Kontrastmittelverstärkter Ultraschall (CEUS) in der Differenzierung von Lipomen und semimalignen atypischen lipomatösen Tumoren : eine prospektive klinische Studie - Mick, Paul; Seeberger, Antonia; Renkawitz, Tobias; Lehner, Burkhard; Hariri, Mustafa; Fischer, Christian; Doll, Julian (Ultraschall in der Medizin, 2023)
Purpose: Soft tissue tumors (STT) are difficult to diagnose accurately, and distinguishing between benign and malignant tumors is challenging. Lipoma is the most common STT, while atypical lipomatous tumors (ALT) can dedifferentiate into malignant lipomatous tumors like grade 1 liposarcoma and require more radical therapy. This study aims to investigate the potential of contrast-enhanced ultrasound (CEUS) to differentiate between lipoma and ALT based on tumor perfusion. Materials and Methods We prospectively examined 52 patients who were scheduled for biopsy for suspected lipoma or ALT. The CEUS examination was performed using SonoVue as a contrast agent to quantify tumor perfusion using VueBox V7.1 software. Peak enhancement (PE), rise time (RT), wash-in perfusion index (WiPI), and wash-out rate (WoR) were used to assess contrast enhancement inside the STT.Results: Among 50 tumors examined, 30 were lipomas, and 20 were ALTs. We found significant differences in perfusion between lipomas and ALTs (PE: 49.22 ± 45.75 a.u. vs. 165.67 ± 174.80; RT: 23.86 ± 20.47s vs. 10.72 ± 5.34 s; WiPI: 33.06 ± 29.94 dB vs. 107.21 ± 112.43 dB; WoR: 2.44 ± 3.70 dB/s vs. 12.75 ± 15.80 dB/s; p<.001). ROC analysis of PE resulted in a diagnostic accuracy of 74% for the detection of an ALT, and 77% for the detection of a lipoma. Conclusion: CEUS may enhance the differential diagnosis of benign lipomas and ALTs, with ALTs showing higher levels of perfusion. If larger prospective studies confirm these findings, CEUS could enhance diagnostic accuracy, guide surgical planning, and potentially reduce unnecessary treatments for patients presenting with ambiguous lipomatous tumors like lipoma or ALT.
Artikel online veröffentlicht: 05. Dezember 2023
Gesehen am 04.03.2024